Mission Accomplished: The ACVP/STP Coalition for Veterinary Pathology Fellows Completes Its Objectives, but Its Legacy and Spirit Live On*. Issue 4 (July 2020) - Adler, Rick; Clark, Elizabeth; Cline, Mark; Conner, Michael; Crabbs, Torrie; Fossey, Stacey; Malarkey, David; Meseck, Emily; Vernau, William; Tornquist, Susan; McDorman, Kevin; Rees, Susan; et al.
After 15 years of existence, the ACVP/STP Coalition for Veterinary Pathology Fellows will dissolve, primarily due to lack of renewed financial sponsorship. While in operation, the Coalition organized 32 new training position for veterinary pathologists, supported by 7.4 M from sponsors, including pharmaceutical and biotechnology companies, contract research organizations, private individuals and allied veterinary pathology support groups. All residual funds will be donated to ACVP and STP with the understanding that the two organizations will use these funds to enhance training by collaborating on outreach efforts, thus maintaining the legacy and spirit of the Coalition.